Si-N-O high-temperature ceramic material as well as ultra-fast synthesis preparation method and application thereof
Through ultrafast high-temperature sintering technology, the problem of Si-N-O high-temperature ceramic materials is solved in a short period of time and the high-performance improvement of the materials is achieved, and it is suitable for aerospace and high-temperature windows and other fields.
Patent Information
- Application Number
- CN202411977840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing preparation process of Si-N-O high-temperature ceramic materials is difficult to achieve densification of ceramic materials in a short period of time, and there are shortcomings in microstructure regulation and performance optimization, especially at the nanoscale, the crystal phase stability and grain boundary engineering control capabilities are limited.
Ultrafast high-temperature sintering technology is adopted to achieve ceramic densification and accurately regulate the microstructure through extremely high temperature rise rates (up to 1000℃/s) and ultra-short sintering time (seconds). The microstructure is reduced, the temperature and stress gradient are improved, and the uniformity and density of the material are improved.
It significantly shortens the sintering cycle, avoids grain coarseness and grain boundary defects, improves the stability and purity of the crystal phase, and improves the overall performance of Si-N-O ceramic materials.
Smart Images

Figure CN119797936A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic non-metallic materials, and in particular to a Si-NO high-temperature ceramic material and an ultra-fast synthesis preparation method and application thereof. Background Art
[0002] With the development of modern aviation industry, the flight speed of spacecraft is constantly increasing, and the demand for high-performance structural and functional integrated materials is also growing. Among them, the application environment requirements of missile radomes, ultra-high-speed aircraft antenna windows and radar and other communication and guidance equipment are very demanding. For example, for aircraft with a Mach number exceeding 5, the radome materials need to withstand high-temperature thermal shocks exceeding 1000℃ or even exceeding 2500℃ under the action of long-term high-speed airflow, which causes general structural materials to fail quickly, so it promotes the rapid development of nitride high-temperature structural materials such as silicon nitride and silicon oxynitride.
[0003] Si-NO ceramic materials have become a research hotspot in the field of high-temperature materials due to their unique crystal structure and chemical properties. Studies have shown that Si-NO ceramics have similar crystal structures and mechanical properties to silicon nitride, but Si-NO ceramics have better thermal shock resistance, lower dielectric constant and dielectric loss, and therefore have become one of the high-performance materials that can replace silicon nitride in the aviation industry. In addition, due to its diversified chemical bonds and structures, Si-NO ceramics thermodynamically exhibit stronger oxidation resistance than materials such as silicon nitride and SiAlON. At the same time, it also has good corrosion resistance in acidic environments, ensuring its long-term stability and reliability in harsh environments. This makes Si-NO ceramics have great application prospects in the field of high-temperature antenna covers.
[0004] Although the existing preparation processes have promoted the development of Si-NO high-temperature ceramic materials to a certain extent, such as the preparation of high-purity and high-density Si-NO ceramic materials through precursor conversion method, vapor deposition method and other technical means, these methods still have significant limitations in practical applications. For example, it is difficult for traditional processes to achieve the densification of ceramic materials in a short period of time, and they are still insufficient in microstructure regulation and performance optimization. Especially at the nanoscale, the existing methods have limited control capabilities in crystal phase stability and grain boundary engineering, which makes it difficult to maintain the performance of the material at high temperature for a long time, affecting its application in aerospace, high-temperature windows and other fields. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned background technology, the present invention adopts ultrafast high-temperature sintering technology to provide a new idea for improving the performance of Si-NO ceramics. The present invention is based on ultrafast high-temperature sintering technology. Due to the extremely high heating rate of more than 1000°C / s and the ultra-short sintering time (seconds), it can effectively avoid excessive grain growth and grain boundary migration, quickly realize ceramic densification, and accurately control the microstructure. Rapid heating not only reduces the temperature and stress gradients, thereby improving the uniformity and density of the material, but also reduces the possibility of phase change or decomposition of the crystal phase in a high-temperature environment by shortening the high-temperature exposure time, thereby improving the stability and purity of the crystal phase. The application of this technology not only effectively improves the overall performance of high-temperature materials, but also provides strong technical support for the demand for materials in special high-temperature environments.
[0006] The first object of the present invention is to provide a method for preparing a Si-NO high temperature ceramic material, comprising the following steps:
[0007] Pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aids are uniformly mixed and then pressed into a green body; in an inert atmosphere, the green body is heated to 1400-1800°C; and kept warm for 8-16s to obtain Si-NO high temperature ceramic material.
[0008] Preferably, the sintering aid is Li2CO3, and the added amount is 1 to 10 wt%.
[0009] Preferably, the pre-oxidized Si3N4 nano-ceramic powder is prepared by heating the Si3N4 nano-ceramic powder at 800-1200° C. for 1-2 hours in an air atmosphere.
[0010] Preferably, the Si3N4 nano-ceramic powder is amorphous, has a particle size of 20nm to 200nm, and a purity of 98% to 99.9%.
[0011] Preferably, when pressing into a green body, the pressure is set to 50-300 MPa and the holding time is 2-10 min;
[0012] The green body is in the shape of a disc, with a radius of 5 to 30 mm and a thickness of 1 to 5 mm.
[0013] Preferably, when uniformly mixing, the pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aid are placed in a ball mill for ball milling;
[0014] During ball milling, the ball-to-powder ratio is 2 to 5:1, the rotation speed is 150 to 360 r / min, and the ball milling time is 10 to 20 hours.
[0015] The second object of the present invention is to provide a Si-NO high temperature ceramic material.
[0016] The third object of the present invention is to provide an application of Si-NO high temperature ceramic material in high temperature resistant structural parts.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention provides a Si-NO high-temperature ceramic material and its ultra-fast synthesis preparation method and application. The present invention adopts a Joule heat heating device to realize ultra-fast synthesis of Si-NO high-temperature ceramic materials. Its extremely high heating rate (up to 1000°C / s or more) and ultra-short sintering time (seconds) significantly shorten the sintering cycle, effectively avoiding the grain coarsening and grain boundary defects caused by long-term high-temperature treatment in traditional sintering methods, and quickly achieving ceramic densification while accurately controlling the microstructure. Ultra-fast high-temperature sintering not only reduces the temperature and stress gradients through rapid heating, thereby improving the uniformity and density of the material, but also reduces the possibility of phase change or decomposition of the crystal phase in a high-temperature environment by shortening the high-temperature exposure time, thereby improving the stability and purity of the crystal phase. These advantages not only improve the performance of Si-NO ceramic materials, but also reduce sintering time and cost, providing a new technical solution for the preparation of high-performance materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD patterns of Si-NO high temperature ceramic materials with different types of sintering aids added;
[0020] Figure 2 This is the SEM image of Si-NO high temperature ceramic material containing L5 sintering aid;
[0021] Figure 3 XRD diagrams of Si-NO high temperature ceramic materials at different sintering temperatures;
[0022] Figure 4 XRD comparison diagram of Si-NO high temperature ceramic materials with different heat treatment methods;
[0023] Figure 5 This is the SEM image of conventionally sintered Si-NO high temperature ceramic material. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0025] The purpose of the present invention is to provide a Si-NO high temperature ceramic material and its ultra-fast synthesis preparation method and application, in view of the limited control ability of existing methods in crystal phase stability and grain boundary engineering, which makes it difficult to maintain the performance of the material at high temperature for a long time, affecting its application in the fields of aerospace, high temperature windows, etc.
[0026] A first aspect of the present invention provides a method for preparing a Si-NO high temperature ceramic material, comprising the following steps:
[0027] Pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aids are uniformly mixed and then pressed into a green body; in an inert atmosphere, the green body is heated to 1400-1800°C; and kept warm for 8-16s to obtain Si-NO high temperature ceramic material.
[0028] The present invention first adopts a powder pressing molding process to mix the pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aids and press them into a green body, and then ultra-fast high-temperature sintering is performed through a Joule heat heating device to prepare Si-NO ceramic materials. The entire sintering process of the present invention to prepare Si-NO high-temperature ceramic materials only takes 10 to 20 seconds, which greatly shortens the sintering time. Ultra-fast high-temperature sintering technology effectively inhibits grain growth and grain boundary migration, quickly realizes ceramic densification and accurately controls the microstructure. Rapid heating not only reduces the temperature and stress gradients, thereby improving the uniformity and density of the material, but also reduces the possibility of phase change or decomposition of the crystal phase at high temperature by shortening the high-temperature exposure time, thereby improving the stability and purity of the crystal phase. These advantages of ultra-fast high-temperature sintering processes effectively improve the performance of the material.
[0029] Wherein, the sintering aid is Li2CO3, and the added amount is 1 to 10 wt%.
[0030] The pre-oxidized Si3N4 nano-ceramic powder is prepared by preserving the Si3N4 nano-ceramic powder at 800-1200° C. for 1-2 hours in an air atmosphere.
[0031] The Si3N4 nano ceramic powder is amorphous, has a particle size of 20nm to 200nm, and a purity of 98% to 99.9%.
[0032] When pressing into a green body, the pressure is set to 50-300 MPa and the holding time is 2-10 min;
[0033] The green body is in the shape of a disc, with a radius of 5 to 30 mm and a thickness of 1 to 5 mm.
[0034] When uniformly mixing, the pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aid are placed in a ball mill for ball milling, achieving mixing and refining treatment;
[0035] During ball milling, the ball-to-powder ratio is 2 to 5:1, the rotation speed is 150 to 360 r / min, and the ball milling time is 10 to 20 hours.
[0036] Exemplarily, a method for preparing an ultra-fast synthesis of Si-NO high-temperature ceramic material is to use a powder pressing process to mix pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aids and press them into a green body, and then use a Joule heat heating device to perform ultra-fast high-temperature sintering to prepare Si-NO ceramic material. Specifically, the following steps are included:
[0037] (1) Pre-oxidation
[0038] A certain mass of Si3N4 nano-ceramic powder is placed in a muffle furnace and pre-oxidized under air atmosphere;
[0039] (2) Add sintering aid
[0040] The powder obtained in step (1) is mixed with a certain proportion of a sintering aid, and then placed in a ball mill for ball milling to achieve sufficient mixing and refinement;
[0041] (3) Pressing
[0042] The mixed powder obtained in step (2) is placed in a special mold and pressed into a green body by a tablet press under a certain pressure;
[0043] (4) Ultra-fast high temperature sintering
[0044] The green body obtained in step (3) is placed between two graphite felts, and the graphite felts are fixed in a Joule heat heating device by a clamp. The experimental chamber is then closed and vacuum filtered, followed by argon gas, and the vacuum filtration and argon gas introduction steps are repeated to achieve a gas washing process, and finally argon gas is introduced to adjust the pressure inside the experimental chamber to standard atmospheric pressure. Finally, the heating parameters are set for ultrafast high-temperature sintering, thereby preparing Si-NO high-temperature ceramic materials.
[0045] The Si3N4 nano-ceramic powder in step (1) is amorphous, with a particle size of 20nm to 200nm and a purity of 98% to 99.9%. The pre-oxidation temperature is 800°C to 1200°C and the time is 1 to 2 hours.
[0046] The sintering aid in step (2) is Li2CO3, and the amount added is 1-10wt%, which is used to reduce the sintering temperature of the sintered material. The ball mill is an agate mill, and the ball-to-powder ratio during the ball milling process is 2-5:1, the rotation speed is 150-360r / min, and the ball milling time is 10-20 hours.
[0047] The pressure in step (3) is set to 50-300 MPa and the holding time is 2-10 min. The green body is in the shape of a disc with a radius of 5-30 mm and a thickness of 1-5 mm.
[0048] The heating parameters of step (4) are: heating rate of 1000-1500°C / s; cooling rate of 1000-1500°C / s; sintering temperature of 1400-1800°C; and holding time of 8-16s.
[0049] A second aspect of the present invention provides a Si—NO high temperature ceramic material.
[0050] A third aspect of the present invention provides an application of a Si-NO high temperature ceramic material in a high temperature resistant structural part.
[0051] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0052] Example 1
[0053] This process is used to treat Si-NO nano-ceramic powders with different types of sintering aids. The specific treatment system is as follows:
[0054] The amorphous silicon nitride nanopowder was placed in a muffle furnace in an air atmosphere at 1000°C for 2 hours for pre-oxidation. The obtained pre-oxidized powder was divided into four parts, and 5wt% Al2O3, 5wt% Al2O3+Y2O3, and 5wt% Li2CO3 were added as sintering aids, named A5, AY5, L5, and a blank control group, named B, and then placed in an agate jar for ball milling for 12 hours at a speed of 180r / min. The ball-to-powder ratio during the ball milling process was 2:1. Among them, the mass ratio of Al2O3:Y2O3 is 1:1;
[0055] The mixed powder was placed in a special tablet pressing mold, the pressure of the tablet press was controlled to 50 MPa, and the holding time was 5 min to obtain a green body.
[0056] The green body was placed between two graphite felts, and the graphite felts were fixed in the Joule heat heating device by a clamp. The experimental chamber was then closed and vacuum filtered, followed by the introduction of argon gas, and the vacuum filtration and the introduction of argon gas steps were repeated to achieve the gas washing process, and finally the argon gas was introduced to adjust the pressure inside the experimental chamber to the standard atmospheric pressure. The heating parameters were set as follows: the heating rate was 1200℃ / s; the sintering temperature was 1700℃; the holding time was 10s; and the cooling rate was 1200℃ / s. The equipment was started for ultrafast high-temperature sintering to prepare Si-NO high-temperature ceramic materials containing different types of sintering aids, named A5-UHS, AY5-UHS, L5-UHS, and B-UHS.
[0057] The polished Si-NO high temperature ceramic material was tested by X-ray diffraction (XRD, Druker D8DISCOVERA25); and the polished sample was tested by scanning electron microscopy (SEM, Tescan Clara GMH) to study its microstructure.
[0058] The XRD images of the Si-NO high temperature ceramic materials containing different types of sintering aids are as follows: Figure 1 As shown in the figure, it can be seen that the blank control group is amorphous; the A5-UHS and AY5-UHS samples show the peak of Si3N4 (#PDF-04-007-3051); the L5-UHS sample shows the peak of Si2N2O (#PDF-00-047-1627). The results show that the single-phase Si-NO high-temperature ceramics were successfully prepared by adding L5 sintering aid.
[0059] Figure 2 This is a SEM image of Si-NO high-temperature ceramic material containing L5 sintering aid. It can be seen from the figure that the sample structure after ultrafast high-temperature sintering shows a high degree of density and uniformity. Specifically, the microstructure of the sample shows that the particles are tightly bound together, and there are almost no obvious pores or defects. This shows that the ultrafast high-temperature sintering process effectively promotes the densification process of the material and significantly improves the microstructural quality of the ceramic material.
[0060] Example 2
[0061] The Si-NO nano-ceramic powder with L5 sintering aid was treated by this process. The specific treatment system is as follows:
[0062] The amorphous silicon nitride nanopowder was placed in a muffle furnace in an air atmosphere at 1000°C for 2 hours for pre-oxidation, the obtained pre-oxidized powder was added with L5 as a sintering aid, and then placed in an agate pot for ball milling for 12 hours at a speed of 180 r / min. The ball-to-powder ratio during the ball milling process was 2:1.
[0063] The mixed powder was placed in a special tablet pressing mold, the pressure of the tablet press was controlled to 50 MPa, and the holding time was 5 min to obtain a green body.
[0064] The green body was placed between two graphite felts, and the graphite felts were fixed in the Joule heat heating device by a clamp. The experimental chamber was then closed and vacuum filtered, followed by the introduction of argon gas, and the vacuum filtration and the introduction of argon gas steps were repeated to achieve the gas washing process, and finally the pressure inside the experimental chamber was adjusted to the standard atmospheric pressure by the introduction of argon gas. The heating parameters were set as follows: the heating rate was 1200℃ / s; the holding time was 10s; the cooling rate was 1200℃ / s; the sintering temperatures were set to 1450℃, 1550℃, and 1650℃, respectively. The equipment was started for ultrafast high-temperature sintering to prepare Si-NO high-temperature ceramic materials at different sintering temperatures, named L5-UHS-1450℃, L5-UHS-1550℃, and L5-UHS-1650℃.
[0065] The polished Si-NO high temperature ceramic material was detected by X-ray diffraction (XRD, Druker D8DISCOVERA25). Figure 3 The XRD images of Si-NO high temperature ceramic materials at different sintering temperatures show that the peaks of Si2N2O appear in the samples of L5-UHS-1450℃, L5-UHS-1550℃ and L5-UHS-1550℃ (#PDF-00-047-1627). According to the experimental results, single-phase Si-NO high temperature ceramics were successfully prepared in the sintering temperature range of 1450℃~1650℃. In the specific experimental process, when the temperature varied within this range, pure Si-NO phase was obtained, and the formation of other impurities was not observed. Therefore, the sintering temperature range of 1450℃~1650℃ is significantly applicable to the preparation of single-phase Si-NO high temperature ceramics.
[0066] Example 3
[0067] The Si-NO nano-ceramic powder with L5 sintering aid was subjected to conventional sintering treatment. The specific treatment system is as follows:
[0068] The amorphous silicon nitride nanopowder was placed in a muffle furnace in an air atmosphere at 1000°C for 2 hours, 5wt% Li2CO3 was added to the obtained pre-oxidized powder as a sintering aid, and then placed in an agate pot for ball milling for 12 hours at a speed of 180r / min. The ball-to-powder ratio during the ball milling process was 2:1.
[0069] The mixed powder was placed in a special tablet pressing mold, the pressure of the tablet press was controlled to 50 MPa, and the holding time was 5 min to obtain a green body.
[0070] The green body was placed in a crucible and put into a tubular furnace. The temperature was increased to 1100°C at a heating rate of 10°C / min in an argon atmosphere, then increased to 1650°C at a heating rate of 5°C / min, kept at this temperature for 2h, then cooled to 1100°C at a cooling rate of 5°C / min, and finally cooled to room temperature at a cooling rate of 10°C / min to obtain a conventionally sintered Si-NO high-temperature ceramic material, named L5-TFS.
[0071] The polished Si-NO high temperature ceramics were tested by X-ray diffraction (XRD, Druker D8DISCOVER A25); and the polished samples were tested by scanning electron microscopy (SEM, Tescan Clara GMH) to study their microstructure.
[0072] Figure 4 The XRD comparison diagram of L5-TFS and L5-UTS shows that conventional sintering will have many impurity peaks, indicating that the product obtained by conventional sintering is impure, while ultrafast high temperature sintering reduces the possibility of phase transition or decomposition of the crystal phase at high temperature by shortening the high temperature exposure time, thereby improving the purity of the product. Among them, L5-UTS refers to the ultrafast sample at 1650°C in Example 2.
[0073] Figure 5 is the SEM image of the L5-TFS sample. Figure 2 By comparing the samples obtained by ultrafast high-temperature sintering, it is obvious that there are significant differences in the microstructure of the two. Specifically, the L5-TFS ceramic material obtained by conventional sintering process shows a larger grain size and higher porosity. This phenomenon shows that during the conventional sintering process, the particles of the material failed to fully densify at a lower sintering temperature and a longer sintering time, resulting in grain growth and ineffective elimination of pores, thus affecting the density and uniformity of the material.
[0074] The comparison of physical properties of samples subjected to conventional sintering treatment in Example 3 and ultrafast high temperature sintering in Example 2 is shown in Table 1.
[0075] Table 1 Comparison of physical properties of ultrafast sintering and traditional sintering samples
[0076]
[0077] As shown in Table 1, the ultrafast high temperature sintering process provided by the present invention can obtain a higher density, which means that there are fewer voids inside the material, the structure is more solid, and the ability to resist mechanical stress is stronger. This is particularly important for aerospace applications, and high-density materials can provide better compressive resistance and stability. The particle size of ultrafast high temperature sintering materials is small, which can improve the overall strength and toughness of the material. Small particle materials usually have higher fracture toughness because there are more grain boundaries and crack propagation is suppressed. For high-temperature window materials, this refined particle structure helps to improve the optical properties and thermal stability of the material. At the same time, the ceramic material prepared by the ultrafast high temperature sintering process has a higher hardness, can better resist friction and wear, and is suitable for use in scenes requiring high wear resistance, such as outer surface materials in aerospace. The materials of the traditional sintering process have a higher elastic modulus and may be suitable for some scenes with higher requirements for material rigidity. However, a higher elastic modulus also means that the material is more brittle, reducing its toughness under impact and high stress environments. Therefore, the ultrafast high temperature sintering process is more suitable for applications requiring higher toughness and strength, such as structural materials for aerospace vehicles. In summary, the ultrafast high-temperature sintering process has significant advantages in improving material density, particle refinement, strength, toughness and hardness. It is especially suitable for applications in the aerospace field that have high requirements for material strength, toughness and wear resistance.
[0078] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a Si-NO high temperature ceramic material, characterized in that: The following steps are involved: Pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aids are uniformly mixed and then pressed into a green body; in an inert atmosphere, the green body is heated to 1400-1800°C; and kept warm for 8-16s to obtain Si-NO high temperature ceramic material.
2. The method for preparing Si-NO high temperature ceramic material according to claim 1, characterized in that: The sintering aid is Li2CO3, and the added amount is 1-10wt%.
3. The method for preparing Si-NO high temperature ceramic material according to claim 1, characterized in that: The pre-oxidized Si3N4 nano-ceramic powder is prepared by preserving the Si3N4 nano-ceramic powder at 800-1200° C. for 1-2 hours in an air atmosphere.
4. The method for preparing Si-NO high temperature ceramic material according to claim 3, characterized in that: The Si3N4 nano ceramic powder is amorphous, has a particle size of 20nm to 200nm, and a purity of 98% to 99.9%.
5. The method for preparing Si-NO high temperature ceramic material according to claim 1, characterized in that: When pressing into a green body, the pressure is set to 50-300 MPa and the holding time is 2-10 min; The green body is in the shape of a disc, with a radius of 5 to 30 mm and a thickness of 1 to 5 mm.
6. The method for preparing Si-NO high temperature ceramic material according to claim 1, characterized in that: When uniformly mixing, the pre-oxidized Si3N4 nano-ceramic powder and a certain proportion of sintering aid are placed in a ball milling jar for ball milling; During ball milling, the ball-to-powder ratio is 2 to 5:1, the rotation speed is 150 to 360 r / min, and the ball milling time is 10 to 20 hours.
7. A Si-NO high temperature ceramic material obtained by the method according to any one of claims 1 to 6.
8. Use of the Si-NO high temperature ceramic material according to claim 7 in high temperature resistant structural parts.
Citation Information
Cited By
Refractory castable for low nickel matte chute and preparation method of refractory castable
CN120398523A